Effects of feeding different probiotic types on metabolic, performance, and carcass responses of Bos indicus feedlot cattle offered a high-concentrate diet - Dias, Bruno Garcia de Carvalho (2023)
Feed additives, such as direct-fed microbials (DFM), are included into feedlot diets to improve rumen fermentation, gastrointestinal tract health, and overall animal performance. Among the strains of interest in DFM products, yeast, lactic acid and bacilli are highlighted. Hence, we hypothesized that the supplementation of different DFM would improve nutrient digestibility, rumen fermentation and performance of feedlot Bos indicus cattle receiving a finishing diet. In Exp. 1, 30 rumen-cannulated Nellore steers were blocked based on initial body weight (BW; 350 ±) 35.0 kg) in 1 of 30 pens and, within each block, animals were randomly assigned to: (1) Control: corn-based diet without DFM , (2) EFSC: CONT + 1 gram/head per day of a DFM based on Enterococcus faecium and Saccharomyces cerevisiae (Probios® Precise, Chr. Hansen A/S, Horsholm, Denmark), and (3) BLBS: CONT + 2 grams/head per day of a DFM based on Bacillus licheniformis and Bacillus subtilis (Bovacillus™ Chr. Hansen A/S). The experimental period lasted 35 days, while between days 30 to 34, total fecal collection was performed and on days 34 and 35, feces and rumen fluid were collected at 0, 3, 6, 9, 12, 15, 18, and 21 h post-feeding. In Exp. 2, 240 Nellore bulls were blocked based on initial body weight (BW; 374 ± 35.3 kg) into 1 of 60 feedlot pens (4 bulls/pen) and pens within blocks were randomly assigned to receive the same treatments as Exp. 1. There were 3 adapting diets and the finishing diet (20% corn silage, 33% ground flint corn, 45% distillers bran plus solubles and 2% minerals and vitamins mixture) that was offered throughout the experimental period (115 days). On day 113, carcass ultrasound evaluations were performed and carcass traits were also obtained upon slaughter on day 117. In Exp.1 the inclusion or type of DFM did not affect either nutrient digestibility or ruminal fermentation parameters (P ≥ 0.40). In contrast, DFM supplementation, regardless of type, yielded a lower mean ammonia concentration (14.7 vs. 15.7 mg/L; P = 0.05). Moreover, ammonia levels were lower in EFSC at 3 and 6 h post-feeding vs. CONT (P ≤ 0.04), but also lower for BSBL vs. CONT at 6 h (P < 0.01). In summary, DFM supplementation, regardless of type, reduced proteolysis, with no effect on other parameters of rumen fermentation. In Exp. 2 no effects were observed on daily DMI (P 0.18) or final BW (P ≥ 0.12). Nonetheless, DFM supplementation, regardless of type, tended to improve ADG (1.57 vs. 1.50 kg; P = 0.10) and FE (145 vs. 140 g/kg; P = 0.07). No further effects were observed on carcass traits measured via ultrasound or at slaughter (P ≥ 0.22). In summary, DFM supplementation, regardless of type, tended to benefit feedlot performance of Bos indicus bulls.